Study of BBB Dysregulation in Neuropathogenicity Using Integrative Human Model of Blood–Brain Barrier - Simöes Da Gama, Coraly; Morin-Brureau, Mélanie (Frontiers in Cellular Neuroscience, 2022)
Blood Brain Barrier (BBB) is a cellular and physical barrier playing a crucial role in homeostasis of the brain extracellular environment. It controls imports into the brain of nutrients and exports toxins and pathogens. Dysregulation of the blood-brain barrier increases permeability and contributes to pathologies including Alzheimer’s disease, Epilepsy and Ischemia. It remains unclear how BBB function is degraded and how it contributes to different syndromes. Initial studies on the role of the BBB in neurological disorders and also techniques to permit entry of therapeutic molecules were made in animals. More recent attention has turned to the use of human models of the BBB which are the subject of this review. During the past years, the complexity and functionality of in vitro BBB models has increased considerably. Initial efforts consisted of simple, static transwell cultures of brain epithelial cells. More recent human cell models, more realistic and better performing are based on microfluidics or organoïds derived from human-derived induced pluripotent stem cells. We consider the architecture of different model generations as well as the cell types used in their fabrication. Finally we discuss optimal model systems to study neurodegenerative diseases, brain glioma, the epilepsies, transmigration of peripheral immune cells and brain entry of neurotrophic viruses and metastatic cancer cells.